MODEL FOR IMPLEMENTATION OF THE ACEH TRADITIONAL ASSEMBLY DEVELOPMENT IN WINNING TRADITION IN ACEH TAMIANG - Syafrizal Syafrizal (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2022)
Marriage customs for the Tamiang tribe are a powerful "guidance tool" to determine attitudes and behavior in everyday interactions. This is in accordance with the expression of this community group, that there is no custom like a ship without a captain. Marriage of children is the main obligation that is very basic for both parents in Tamiang tribal marriages since birth, in general, parents are obliged to educate (nurturing), circumcise, then find a mate and carry out marriage ceremonies for their children. The method used is descriptive research method with qualitative data analysis and data collection techniques used are interview techniques. Based on the results of the discussion, the authors conclude that the functions of the Aceh Customary Council have been carried out in accordance with the applicable procedures to be applied to the community, but in reality the community gives a different argument that traditional institutions and the government do not fully carry out their duties to the fullest. This uncertainty actually occurs in many aspects, including in addition to the above, it turns out that the developmental factor of the times is one of the most important things that causes this change and the traditional ancestors who have passed away as main role models. Under these circumstances, adat is still carried out as it should be, although it is felt here and there that there are new procedures emerging so that the initial procedures did not run effectively and efficiently